2021
DOI: 10.1001/jama.2021.9907
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Differences in Health Status and Health Care Access and Affordability by Race and Ethnicity in the United States, 1999-2018

Abstract: IMPORTANCEThe elimination of racial and ethnic differences in health status and health care access is a US goal, but it is unclear whether the country has made progress over the last 2 decades. OBJECTIVE To determine 20-year trends in the racial and ethnic differences in self-reported measures of health status and health care access and affordability among adults in the US.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
118
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 27 publications
4
118
1
Order By: Relevance
“…In the current study, the authors reported that the majority of ACP discussions were held by a minority of surgeons and that different institutions and study sites had vastly different rates of ACP documentation. 1 These results are further supported by findings of large variations between physicians and hospitals in ACP reporting in hospitalized frail older adults. 4 These variations in practices at different institutions suggest that it is possible to improve rates of preoperative ACP discussion.…”
Section: Commentarymentioning
confidence: 61%
See 4 more Smart Citations
“…In the current study, the authors reported that the majority of ACP discussions were held by a minority of surgeons and that different institutions and study sites had vastly different rates of ACP documentation. 1 These results are further supported by findings of large variations between physicians and hospitals in ACP reporting in hospitalized frail older adults. 4 These variations in practices at different institutions suggest that it is possible to improve rates of preoperative ACP discussion.…”
Section: Commentarymentioning
confidence: 61%
“…Given the consensus that ACP is important in the care of older adults undergoing high-risk surgery, one would assume that preoperative ACP discussion is a standard of practice among surgeons and their aging patients. However, in a secondary analysis of a randomized control trial testing a patient-mediated intervention to improve preoperative communication, Kalbfell et al 1 showed that ACP discussions rarely take place prior to major surgery in older adults. This finding highlights the significant discrepancy between the belief that ACP is important, and the actual rate that it is practiced, in older patients undergoing high-risk surgery.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations